Method of SWOT-analysis when planning investment and innovation processes in the enterprise - Акулюшина, Марина Олександрівна (Technology audit and production reserves, 2015)
The present article deals with the application of the SWOT- analysis technique in practice of effectiveness evaluation of investment and innovative projects in the industry. The aim of the article was to justify the need for such analysis to determine the environmental factors of development projects and identify those that require further attention from the developers of the project initiators. The study was carried out a retrospective analysis of the literature to define the scope of SWOT- analysis techniques. It was found that most of the methodology used to select the strategic direction of the company and provide an objective assessment of the current status of the enterprise management as a whole. Also this technique is applied in practice in the development of anti-crisis measures. The experience hasn’t been submitted as regards the application of such assessment in the planning of investment and innovation processes in the enterprise application. That is why the author proposes to use this technique as part of the pre-planning research investment and innovation projects, which are proposed for consideration by the management companies or potential investors. Results that obtained from the practical application confirm the necessity and reasonableness of the use of this technique during the preplanning research investment and innovation projects.